Al-Simth Al-Majid: Melacak Pengaruh Syaikh Ahmad Al-Qusyaisyi terhadap Tradisi Sufi di Aceh (Pendekatan Analisis Tekstual Hadits) - Nuraini Nuraini (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2019)
Syattariyah tarekat is a popular tarekat in Aceh, especially during the Islamic kingdom of Aceh Darussalam under the leadership of the Queen. Abd. Rauf al-Singkel is considered the first carrier of the Syattariyah order. However, the network of the Syattariyah ulema from Abd. Rauf al-Singkel in Aceh has yet to be found. Therefore, it was assumed that the Syattariyah order existed between the 19th and 20th centuries in Aceh had nothing to do with Abd. Rauf al-Singkel. This statement implies that the Syattariyah's lineage from Sheikh Ahmad al-Qusyasyi in Aceh has lost. Abd. Sheikh Ahmad al-Qusyasyi has conferred Rauf al-Singkel as a messenger to spread the tarekat in the Indonesian archipelago. It is interesting to examine the influence of Sheikh Ahmad al-Qusyasi on the Syattariyah order developed in Aceh. Thus, the question was raised whether the trace of Sheikh Ahmad al-Qusyasyi’s influence on the Sufi tradition in Aceh still exists. One way to clarify the influence is by examining the Syattariyah order in Aceh through Acehnese Sufi figures. By looking at the lineage of the sanad they use, we would be able to determine if their sanad reaches Sheikh Ahmad al-Qusyasyi. The genealogical paths found in the current study and that of Oman Fathurrahman's show that the sanad of the Syattariyah tarekat in Aceh attained to Sheikh Ahmad al-Qusyasi. Thus, it can be concluded that the Syattariyah order developing in Aceh was originated from Sheikh Ahmad al-Qusyasyi, either through Abd. Rauf al-Singkel or other Acehnese scholars.Abstrak: Syattariyah merupakan tarekat yang populer di Aceh, terutama pada masa kerajaan Islam Aceh Darussalam di bawah pimpinan Ratu/Sulthanah. Abdurrauf al-Singkel dianggap sebagai pembawa pertama tarekat Syattariyah. Namun hingga saat ini belum ditemukan jaringan keulamaan tarekat Syattariyah yang berkembang di Aceh dari silsilah Abdurrauf al-Singkel. Bahkan tarekat Syattariyah yang ada dalam abad XIX dan XX di Aceh dianggap tidak ada hubungannya dengan Abdurrauf al-Singkel. Pernyataan ini tampak menunjukkan terputusnya silsilah tarekat Syattariyah dari Syaikh Ahmad al-Qusyasyi di Aceh. Padahal Abdurrauf al-Singkel sendiri merupakan khalifah yang ditunjukkan langsung oleh Syaikh Ahmad al-Qusyasyi untuk menyebarkan tarekat di wilayah Nusantara. Oleh karena itu, artikel ini ingin mengkaji pengaruh Syaikh Ahmad al-Qusyasi terhadap perkembangan tarekat Syattariyah di Aceh. Apakah masih ada pengaruh Syaikh Ahmad al-Qusyasyi dalam tradisi sufi di Aceh?. Hasil penelitian ini menunjukan bahwa silsilah sanad tarekat Syattariyah yang berkembang di Aceh semua bersumber dari Syaikh Ahmad al-Qusyasi. Dengan demikian dapat simpulkan bahwa tarekat Syattariyah yang berkembang di Aceh dari jalur silsilah adalah tarekat Syattariyah yang bersumber dari Syaikh Ahmad al-Qusyasyi, termasuk Abdurrauf al-Singkel pada masanya maupun beberapa ulama Aceh lainnya.